Use of a novel phosphatase test for simplified identification of species of the tribe Proteeae. - Pompei, R (1990)
Phosphatase activity of 334 isolates of the tribe Proteeae carefully identified to species level has been evaluated by using both a number of conventional tests and three versions of the novel methyl green-phenolphthalein (MGP) method (G. Satta. R. Pompei, G. Grazi, and G. Cornaglia, J. Clin. Microbiol. 26:2637-2641, 1988). We found that the different species of Proteeae show different and easily distinguishable. behaviors by the MGP method, while all of them behave in a uniform way in the conventional tests. On studying the mechanism underlying these different behaviors, we found that the phosphatase activity of Morganella morganii and Providencia stuartii is higher than that of all other members of the family Enterobacteriaceae. Furthermore, we found that all P. stuartii strains display the property (shared by virtually none of the other species of Enterobacteriaceae) of excreting significant amounts of phosphatase. This extracellular activity is reliably detected by the MGP method but not by conventional tests. Finally, by exploiting the peculiar phosphatase activity of this tribe, as revealed by the MGP method, we devised a simple scheme for routine identification of the species of Proteeae and evaluated its reliability by comparing it with three commonly used commercial kits. The new scheme proved much simpler, but also more reliable, since identifications obtained by this method were in almost complete accord (99%) with those of the reference identification schemes, while in the commercial systems examined the percentage of errors ranged from 13 to 14 in the identification of Providencia species.